Implementasi Internet Of Aquaculture (IoA) untuk Deteksi Kualitas Lingkungan Secara Cepat dalam Upaya Pemberdayaan Kelompok Pembudidaya Ikan Koi Di Blitar - Yuni Kilawati; Yunita Maimunah; Adharul Muttaqin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
The increasing number of Koi ornamental fish interested around the world, this fish farming business is increasingly developing. Blitar is one of the geographically suitable areas to develop Koi fish farming. The resulting production has a quality of Koi better than from other countries. Cultivation models and techniques developed are also increasingly advanced, but often cultivators have disease problems stemming from decreasing environmental quality that are not handled early. This attracted the Brawijaya University Doctoral community service team to help find solutions to these problems.